Elucidation of the biosynthetic pathway of B-group vitamins via genome mining of food-derived Bacillus velezensis VTX20 - Tung, Quach Ngoc; Nguyen, Vu Thi Hanh; Xuan, Le Thi Thanh; Ha, Chu Hoang; Tien, Phi Quyet (Academia Journal of Biology, 2021)
B-vitamins are micronutrients that play an important role in various cellular processes of organisms, which are only synthesized by plants, yeasts, and bacteria. Since animals and humans lack the ability to synthesize B-vitamins, supplements of vitamins from dietary and the B-vitamin producing bacteria are required. In this study, we, for the first time, shed some light on biosynthetic pathways involved in folate (vitamin B9), riboflavin (vitamin B2), and biotin (vitamin B7) production in Bacillus velezensis VTX20. The genome-wide comparison revealed that B. velezensis VTX20 shared high similarities with B. tequilensis KCTC 13622, B. subtilis 168, B. amyloliquefaciens DSM 7. Genomic analysis revealed the presence of a complete folate biosynthesis pathway in which some core components were not found in most Bacillus species. Moreover, strain VTX20 also had the metabolic pathways for riboflavin and biotin that are important probiotic traits. These results highlighted that B. velezensis VTX20 is a producer of B-vitamins, which can be applied further in the agricultural biotechnology industry.